2015
DOI: 10.1108/nlw-05-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review informing library and information professionals’ emerging roles

Abstract: Purpose – This paper aims to provide a systematic review of the specific roles information professionals have adopted in the past 14 years. It aims to identify the roles reported in the literature concerning developments in the Library and Information Science (LIS) profession. Design/methodology/approach – This study adopted the method of systematic review. Searches were conducted in February and March 2014 on different LIS databases. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 101 publications
(150 reference statements)
3
51
0
5
Order By: Relevance
“…Studies of existing relationships imply that partnership is both a powerful input and output of librarians' relationships with academics; Hardy & Corrall (2007) found that a partnership (or 'consulting') approach leads to the most effective communication; Webb et al (2007) felt that effective professional support leads to academics perceiving librarians as "counsel, colleague and critical friend" (p144). Vassilakaki & Moniarou-Papaconstantinou (2015), in a systematic review of emerging librarian roles, identify multiple roles ('embedded librarian', 'information consultant') which develop such partnership approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of existing relationships imply that partnership is both a powerful input and output of librarians' relationships with academics; Hardy & Corrall (2007) found that a partnership (or 'consulting') approach leads to the most effective communication; Webb et al (2007) felt that effective professional support leads to academics perceiving librarians as "counsel, colleague and critical friend" (p144). Vassilakaki & Moniarou-Papaconstantinou (2015), in a systematic review of emerging librarian roles, identify multiple roles ('embedded librarian', 'information consultant') which develop such partnership approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding is in line with Hallmark and Lembo (2003). This might be attributed to the public's lack of awareness of LIS as a possible educational choice Choice of Library and Information Science and misunderstanding of the roles and responsibilities of information professionals ( Jones, 2010;Vassilakaki and Moniarou-Papaconstantinou, 2015) (see Figure 9). Hallmark and Lembo (2003) addressed a different population, scientists and explored the reasons why they decided to change careers and pursue the LIS discipline.…”
Section: Career Change To Lismentioning
confidence: 99%
“…Et voilà peut-être le plus grand défi auquel doivent se mesurer les formateurs en SI! On trouve dans la littérature professionnelle et scientifique des 15 dernières années un grand nombre d'articles et de monographies portant sur les caracté-ristiques et les compétences attendues du nouveau professionnel; Vassilakaki et Moniarou-Papaconstantinou (2015) en ont repéré près de 600 et utilisé 114 pour prépa-rer la plus récente synthèse publiée sur le sujet.…”
Section: Diversité Des Objectifs Et Des Attentesunclassified